Ereignis e dedizione dell’essere - Samonà, Leonardo (Quaestio, 2024)
Abstract According to Heidegger, with the circle we enter by asking about what is first, not only the way of proceeding changes, but also and above all the goal of philosophical investigation. The early awareness of the “metamorphosis” internal to the foundation of thought allows Heidegger to take up in an original way the metaphysical question of being qua being, that is “in itself” (the ousia). On the one hand, this results in a destabilization of the structure of philosophy: what is first enters in the thought as such, that is, distinguishing itself from it and escaping its grasp. But the result of this destabilization is neither the emancipation of philosophy from its task of foundation, nor the resignation to the impossibility of fulfiling it. Rather, it is the discovery that ≪asking arises from finding and develops “only” this≫; and that the principle of thought is essentially the “way to itself” and has its “proper” in “proximity”. Heidegger collects in the term Ereignis the internal logic of giving itself by the being, from which the philosophical question of the foundation arises.